POLSKO-ROSYJSKIE KONTAKTY FILMOWE - Mocarz-Kleindienst, Maria (Acta Neophilologica, 2016)
Polish-Russian film relations have a long history. However, they have strongly intensified for the last decade, largely due to political changes. This paper provides an overview of the most representative projects promoting the film industries of the two countries organised both in Poland and in Russia, such as the Sputnik Russian Film Festival in Poland and the Wisła Polish Film Festival in Russia. It also presents the most important joint cinema projects, including Polish-Russian co-productions, Polish films with Russian actors and Russian films with Polish actors.